Предмет: Математика,
автор: markegorov01
(1,5)^3 × (2,25)^-1,5 × (0,75)^-1 × [(-1/3)^-2 + (-1/2)^-1 - (2 3/7)^0]
Приложения:
Ответы
Автор ответа:
0
Ответ:
8
Пошаговое объяснение:
1,5^3 •2,25^(-1,5) •0,75^(-1) •((-1/3)^(-2) +(-1/2)^(-1) -2 3/7)^0)=(3/2)^3 •(4/9)^(3/2) •4/3 •((-3)^2 -2-1)=3^3 •2^(-3) •2^3 •3^(-3) •2^2 •3^(-1) •(9-3)=3^(3-3-1) •2^(-3+3+2) •3•2=3^(-1+1) •2^(2+1)=3^0 •2^3=1•8=8
Похожие вопросы
Предмет: География,
автор: sabelnikove955
Предмет: Физика,
автор: yahajahh120
Предмет: История,
автор: demanbajtakov17
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: SmilleCat